EDUKASI PENGGUNAAN BERBAGAI JENIS HEADSET PADA GENERASI Z - Triansyah, Irwan; Nadia Purnama Dewi,; Ade Teti Vani,; Dessy Abdullah,; Aryaldi Zulkarnaini, (Nusantara Hasana Journal, 2024)
Generation Z is a group that is very familiar with technology, especially using headsets for various purposes such as listening to music, studying, and playing games. However, a lack of knowledge about the correct use of headsets can cause multiple health problems such as hearing loss and physical discomfort. This community service aims to educate Generation Z, especially SMP YARI Padang students, about how to use various types of headsets safely and comfortably. Method: The method includes presentations, interactive discussions, and direct demonstrations in selecting and using an appropriate headset. Results: As a result of the education, students have a better understanding of the various types of headsets and their impact on hearing health and the ergonomics of their use. Students can also identify the type of headset that best suits their needs and understand the importance of limiting usage time to prevent health problems. After counseling, it was found that almost 95% of students were able to answer questions correctly. Hopefully, this education will help Generation Z understand more about selecting and using headsets and minimize the health risks they may face.